Mixed Medullary-Follicular Carcinoma of the Thyroid - Maasumeh Tohidi; Gholamreza Pourbehi; Mohammad Bahmanyar; Seyed Sajjad Eghbali; Mohammadreza Kalantar Hormozi; Iraj Nabipour (Case Reports in Endocrinology)
Introduction. Mixed medullary-follicular thyroid carcinoma is an uncommon tumor that consists of both follicular and parafollicular cells. Case. We report a 43-year-old woman with a palpable mass in the right side of the neck. Fine needle aspiration suggested a diagnosis of high grade anaplastic carcinoma that has been associated with papillary features. Total thyroidectomy was done in which histopathological examination showed diagnosis of medullary carcinoma. Immunohistochemical staining was positive for chromogranin, calcitonin, and thyroglobulin in tumoral cells. Conclusion. Mixed medullary-follicular thyroid carcinoma is a rare tumor. Diagnosis of these tumors with fine needle aspiration is very difficult and may lead to misdiagnosis. It is necessary to correlate the cytological finding with serum calcitonin and thyroglobulin. Also immunostaining for calcitonin and thyroglobulin confirms diagnosis.